2013
DOI: 10.7554/elife.00868
|View full text |Cite
|
Sign up to set email alerts
|

Direct live imaging of cell–cell protein transfer by transient outer membrane fusion in Myxococcus xanthus

Abstract: In bacteria, multicellular behaviors are regulated by cell–cell signaling through the exchange of both diffusible and contact-dependent signals. In a multicellular context, Myxococcus cells can share outer membrane (OM) materials by an unknown mechanism involving the traAB genes and gliding motility. Using live imaging, we show for the first time that transient contacts between two cells are sufficient to transfer OM materials, proteins and lipids, at high efficiency. Transfer was associated with the formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
89
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 28 publications
2
89
0
Order By: Relevance
“…For example, chains of vesicles in Myxococcus xanthus are important for cell-cell signaling; outer membrane exchange between cells facilitated by these structures can help manage stress at the population level (9,10). Cryo-electron microscopy (cryo-EM) images of the M. xanthus vesicle chains show characteristics similar to those we observed for S. oneidensis nanowires using atomic force microscopy and fluorescence microscopy (8,11,12). Recently, tube-like membrane connections have been identified between Desulfovibrio vulgaris and Clostridium acetobutylicum, as well as between Escherichia coli and Acinetobacter baylyi, for the purpose of exchanging cellular materials and cross-feeding between each pair of species (13,14).…”
supporting
confidence: 51%
“…For example, chains of vesicles in Myxococcus xanthus are important for cell-cell signaling; outer membrane exchange between cells facilitated by these structures can help manage stress at the population level (9,10). Cryo-electron microscopy (cryo-EM) images of the M. xanthus vesicle chains show characteristics similar to those we observed for S. oneidensis nanowires using atomic force microscopy and fluorescence microscopy (8,11,12). Recently, tube-like membrane connections have been identified between Desulfovibrio vulgaris and Clostridium acetobutylicum, as well as between Escherichia coli and Acinetobacter baylyi, for the purpose of exchanging cellular materials and cross-feeding between each pair of species (13,14).…”
supporting
confidence: 51%
“…Other studies have demonstrated a transfer of outer-membrane proteins between the two strains of Myxococcus xanthus, a wildtype strain acting as donor cell and a mutant strain acting as recipient for the product of the missing gene 41,42 . A form of bacterial communication has been described between adjacent cells via connecting 'nanotubes', even between Gram-positive and Gram-negative bacteria 23 , which could resemble the cell-cell interaction between C. acetobutylicum and D. vulgaris described here, where we show a bidirectional exchange.…”
Section: Discussionmentioning
confidence: 99%
“…To identify whether these intercellular connections consist of membrane-derived lipids, 9-h-old interspecific cocultures of the cross-feeding mutants A. baylyi DhisDDtrpR and E. coli DtrpBDhisL were labelled with the lipophilic dye DiO that intercalates in lipid membranes 20 . Subsequent in vivo fluorescent imaging of the otherwise mCherry-labelled cells should pinpoint the potential lipid-based nature of extracellular appendages by their green fluorescence.…”
Section: Construction Of Synthetic Cross-feeding Interactionsmentioning
confidence: 99%
“…Such mechanisms include, for example, the production of outer membrane vesicles, as they are used by many bacterial species to deliver cargo to other cells [12][13][14][15][16] . Alternatively, bacterial cells may connect via channels 17 , nanotubes 18 , pili 19 or transiently fuse their outer membrane 20 to transfer cytoplasmic components or outer membrane materials.…”
mentioning
confidence: 99%
See 1 more Smart Citation